Visualization and analysis of the gasohol blends fuel spray pattern - Muhammad Ashraf, Ali Zubir (2010)
Operation of flex fuel vehicles requires operation with a range of fuel properties. The significant differences in the heat of vaporization and energy density of E0-E100 fuels and the effect on spray development need to be fully comprehended when developing engine control strategies. Limited enthalpy for fuel vaporization needs to be accounted for when developing injection strategies for cold start, homogeneous and stratified operation. Spray imaging of gasoline injectors with fuels ranging from E0 to E75 was performed in an ambient pressure and temperature.